Pengaruh Mental Imagery Terhadap Regulasi Emosi Atlet Sepatu Roda - Latifatunisa Herfianty Putri; Miftakhul Jannah (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aims to determine the effect of mental imagery training on the regulation of emotions in roller skating athletes. The main question of this study is whether mental imagery training can significantly improve athletes' emotion regulation abilities. The research used a quantitative method with a pseudo-experimental design (one group pretest–posttest design). The research subjects consisted of seven roller skating athletes who participated in the 2025 POMNAS championship. The data collection instrument used the Impulse and Emotion Regulation Questionnaire for Sports (IERQ-4S) which consisted of 10 items with a Likert scale of 1–4. Data analysis was carried out using the Paired Sample t-Test. The results showed a significant increase in the ability to regulate emotions after the mental imagery intervention with values of t = -19.598 and p = 0.001 (< 0.05). The average score increased from 27.57 in the pretest to 36.86 in the posttest, demonstrating the effectiveness of training in helping athletes manage emotions and maintain psychological stability. In conclusion, mental imagery training has a positive and significant effect on improving the emotional regulation of roller skating athletes, so that it can be used as a psychological strategy in athlete coaching programs. Keywords: mental imagery, emotion regulation, sports psychology, roller skating athletes, psychological intervention  pembinaan atlet.